Sistem Informasi Penggajian Guru dan Karyawan Berbasis Web di Yayasan Pendidikan Silaturahim Jatikarya - Ilham Mulyana, Muhamad; Primasari , Dewi; Kamilah , Nurul (Jurnal Etnik: Ekonomi-Teknik, 2024)
The Jatikarya Silaturahim Education Foundation (YPSJ) is a boarding school-based educational institution, the workforce is divided into teachers and employees with their respective job duties. The system that is currently running processes data using Microsoft Excel. However, there are still many obstacles, such as recording salary calculations consisting of position allowances, functional allowances, transportation allowances, special allowances and reductions in salary deductions. So reports and receipt of information to superiors and employees are often late and errors occur. The aim of this research is to analyze payroll processing and calculations, by designing and building a payroll information system that can be managed automatically based on theoretical foundations. Collecting observation data results using writing methods and tools using document flow charts, context diagrams, data flow diagrams, data dictionaries, normalization and table relationships. Research implementation uses the PHP programming language and database creation uses MySQL. In application testing, black-box testing is used, which is a method of designing test data based on software specifications. It is hoped that this teacher and employee payroll information system can be a solution that can be used to simplify the admin process in managing and providing data information accurately and time efficiently.